Transformation of Religious Education System in Postcolonial Morocco - N. A. Zherlitsina (Научный диалог, 2024)
This article examines the changes in the Islamic education system in the Kingdom of Morocco during the period of independent development. The primary objective of the study is to explore the unique Moroccan experience of integrating two distinct educational systems: Islamic and secular. The Moroccan practice may serve as a valuable example in light of the pressing issues of countering Islamist radicalism and extremism. The paper discusses the historical context, the reasons for governmental and societal attention to this topic, and the key stages in the transformation of the religious education system. An analysis of the prospects for Islamic education in contemporary Moroccan society is also provided. The research draws on official documents from the Moroccan Ministry of Education, national legislation, and royal speeches addressing this issue. It is demonstrated that throughout the second half of the 20th century and into the early decades of the 21st century, Moroccan authorities viewed the Islamic education system as a primary tool for influencing the political sphere, a key institution for shaping national culture, and a means to strengthen loyalty to the state. It is asserted that reforms in the Islamic education system in Morocco have enabled it to become more modern and relevant while simultaneously preserving the cultural traditions and uniqueness of the country.